(untitled) (TAMADDUN NURI JURNALI, 2024)
This article provides comments on the role of highly educated personnel in the development of agriculture. It also analyzes reforms aimed at meeting the need for qualified personnel in the development of farms and the cluster system of the Surkhandarya region.